Controlled Drug Delivery by Polylactide Stereocomplex Micelle for Cervical Cancer Chemotherapy - Niu, Kai; Yao, Yunming; Xiu, Ming; Guo, Chunjie; Ge, Yuanyuan; Wang, Jianmeng (Frontiers in Pharmacology, 2018)
A stable doxorubicin (DOX)-loaded stereocomplex micelle drug delivery system was developed via the stereocomplex interaction between enantiomeric 4-armed poly(ethylene glycol)–poly(D-lactide) and poly(ethylene glycol)–poly(L-lactide) to realize control drug release and improve tumor cell uptake for efficient cervical carcinoma therapy. All these DOX-loaded micelles including poly(D-lactide)-based micelle (PDM/DOX), poly(L-lactide)-based micelle (PLM/DOX), and stereocomplex micelle (SCM/DOX) exhibited appropriate sizes of ~ 100 nm for the enhanced permeability and retention (EPR) effect. In addition, compared to PDM/DOX and PLM/DOX, SCM/DOX exhibited the slowest DOX releaser, highest tumor cell uptake and the most efficient tumor cell suppression in vitro. Moreover, the excellent tumor inhibiting rates of the DOX-loaded micelles, especially SCM/DOX, were verified in the U14 cervical carcinoma mouse model. Increased tumorous apoptosis and necrosis areas were observed in the DOX-loaded micelles treatment groups, especially the SCM/DOX group. In addition, all these DOX-loaded micelles obviously alleviated the systemic toxicity of DOX. As a result, SCM can be a promising drug delivery system for the future therapy of cervical carcinoma.